Linking Corporate Social Responsibility (CSR) and affective organizational commitment: Role of CSR strategic importance and organizational identification - Umer Zaman; Raja Danish Nadeem (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Executives around the world continueto explicitly test the business value of corporate social responsibility and organizational commitment that ultimately transformbusinesses to superior performance and sustainable success. The purpose of this study isto empirically examine the impact of corporate social responsibility (CSR) on affective organizational commitment (AOC) under moderating condition of CSR strategic importance and mediating effect of organizational identification (OI). Survey-based primary data was collected from 229 participants from the telecom sector. We used sequential methodological approach for developing a conceptual framework (through qualitative research) and then structural equation modeling (SEM) (as aquantitative technique) for hypotheses testing and assessment of our proposed model. Our SEM findings revealthat CSR has a significantly positive effect on AOC. Findings conclude that organizational identification significantly mediate the CSR-AOC relationship; while CSR strategic importance significantly and positively moderate the CSR effect on AOC. Our study findings offer novel contribution to theory and practice by introducing a holistic model of affective organizational commitment involving CSR and organizational identification. We developed a better understanding for business leaders aboutthe dynamics of CSR (practices and strategic importance) in shaping member's affective commitment in organizations.
Keywords: 330; corporate social responsibility; organizational commitment; organizational identification; CSR strategic importance; telecom sector